Penerjemahan Bahasa Inggris Titelatur dan Nomenklatur Kementerian Perhubungan dalam Konteks Hubungan Internasional - Wilujeng, Ratna Sari (Kementerian Sekretariat Negara Republik Indonesia, 2016)
This article aims to describe the dissimilar English translation versions of the designation and nomenclature of the Ministry of Transportation. This translation is important due to the Ministry of Transportation’s relations with foreign institutions in international regulation of transportation safety and in economic business. The analysis is conducted with respect to administrative correspondence, officials’ business cards, and other electronic media. The results show that, in fact, everyone, every organization and every institution tend to have its own version of English translation of the designation and nomenclature of the Ministry of Transportation. Hence, there is a necessity for the legality of English translation of the designation and nomenclature of the Ministry of Transportation. Keywords: designation, nomenclature, Ministry of Transportation, English translation